Online marketing : a user's manual - Newlands, Murray (Wiley-Interscience, 2011)
What is SEO anyway?What does affiliate marketing actually mean?Who actually watches corporate videos online?What's the difference between a digital brand and a 'real' one?The internet has changed how most people do their jobs beyond recognition. Sometimes that's quite exciting, and other times it's pretty frightening. Online Marketing: A Users Manual has all the answers. Murray Newlands, an international expert on making the most of online marketing, tells you the basics behind the key aspects of online marketing, how you can use it, how you can use it even better, and looks at what the future.